Responses of a federally threatened shorebird to trophic downgrading and expansion of domestic cats (Felis catus) - Christy N. Wails; Kathleen M. Black; Sarah M. Karpanty; Henrietta A. Bellman; Audrey DeRose-Wilson; Sharon S. Dorsey; Katie W. Oliver; Shannon J. Ritter; Samantha G. Robinson; Hope L. VanDerwater; Daniel H. Catlin; James D. Fraser (Biological Invasions, 2025)
Along U.S. Atlantic and Gulf Coast barrier islands, red foxes ( Vulpes vulpes ) are top predators that are thought to impact smaller mesopredators and depredate beach-nesting birds. Starting in 2015, sarcoptic mange epizootics among red foxes led to their eventual temporary extirpation from most of Fire Island, NY, USA. We monitored the subsequent changes to the mammalian predator community on this barrier island and explored the impacts to piping plovers ( Charadrius melodus ), a federally threatened shorebird. We deployed trail cameras and quantified detection rates of four common shorebird predators (red foxes, northern raccoons Procyon lotor , Virginia opossums Didelphis virginiana , and invasive domestic cats Felis catus ), and tested for effects of predator activity and density on piping plover nest and brood survival. Following the loss of red foxes, northern raccoon and Virginia opossum activity remained relatively unchanged, while cat activity increased. The cat population grew from 14 to 42 individuals across the three study areas, and cats later became the most frequently detected mammalian predator. The loss of red foxes was associated with increased plover nest survival (β ± SD = 1.08 ± 0.55), though the increase of cats in later years was associated with a strong, negative decline in nest survival (β ± SD = −3.08 ± 1.28). Plover brood interval survival was negatively correlated with cat density (β ± SD = −0.50 ± 0.14) but not with red foxes. We underscore the importance of monitoring invasive predators during periods of trophic downgrading, which may have delayed impacts to native fauna.